Streamlined life cycle assessment of packaging waste in coffee preparation and consumption - Moresi, Mauro; Cimini, Alessio (Italian Journal of Food Science, 2025)
The escalating environmental concerns surrounding packaging waste and the drive for circularity, as highlighted by the European Union’s (EU) Packaging and Packaging Waste Regulation, necessitate a thorough assessment of consumer products. This study characterizes coffee production and consumption, including its environmental impact, and conducts a streamlined life cycle assessment (LCA) focused on the use and post-consumer phases of diverse coffee formats to quantify packaging waste per coffee cup and evaluate associated environmental burdens. Eight coffee formats—flexible multilayer bags, pads, and various capsules (aluminum [Al], polypropylene [PP], polyethylene-aluminum-polyethylene terephthalate [PE-Al-PET], polylactic acid [PLA], and paper), alongside innovative coffee balls—and their corresponding brewing systems (Moka pot, espresso machine, pad/capsule machine, and reusable capsules) were considered. Utilizing a functional unit of 720 kg of roasted and ground coffee (RGC), the environmental impact was assessed using the EU product environmental footprint (PEF) methodology. Results conclusively demonstrate that traditional brewing systems using RGC from multilayer bags (PEF: 613±10 nPt/cup) are significantly less impactful than single-serving options such as coffee balls (PEF: 1,675±25 nPt/cup) and particularly capsule/pad systems, such as coffee pads (PEF: 2,895±581 nPt/cup) or PP capsules (PEF: 2,777±23 nPt/cup) across normalized and weighed PEF scores. Detailed analysis further reveals substantial differences in organic and packaging waste generation (e.g., the overall waste from multilayer bags: ≈12 g/ cup vs. coffee pads: 22.1 g/cup), carbon footprint (e.g., greenhouse gas [GHG] for multilayer bags: 8.2 g CO2e/ cup vs. PP capsules: 41 g CO2e/cup), fossil resource use, and water use per single coffee cup, underscoring the disproportionate environmental burden of single-serve options. While traditional systems demand more consumer efforts (e.g., filling portafilters and discarding spent ground coffee), their environmental benefits are clear and quantifiable. This study identifies critical environmental hotspots and provides evidence-based recommendations to align coffee consumption with evolving the EU regulations, advocating for more sustainable practices in product design and consumer choice.